1992
DOI: 10.1182/blood.v79.2.503.503
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of cytokines in human blood monocyte subpopulations [see comments]

Abstract: Cytokine expression was analyzed in CD14++ regular monocytes and in the novel subset of CD14+/CD16+ small monocytes. Biologic activity for tumor necrosis factor (TNF), interleukin-1 (IL-1), and IL-6 in the supernatant of elutriator-enriched, cell sorter-purified small monocytes was about 10-fold lower compared with regular monocytes when stimulated with lipopolysaccharide (LPS) for 12 hours. In CD14++ regular monocytes levels were 1,157 U x 10(-3)/mL, 158 U/mL, and 1,337 U/mL for TNF, IL-1, and IL-6, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…There is also a subset of peripheral blood monocytes that expresses CD14 less intensely, but with an increased expression of CD16 on the cell membrane (CD14 + CD16 + ). 32,33 This subset also seems to be distinct from regular blood monocytes, since they produce less TNF, IL-1b and IL-6 34 and may represent an early stage of differentiation towards alveolar macrophages. Another possibility is that GM-CSF promotes differentiation of monocytes towards antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 98%
“…There is also a subset of peripheral blood monocytes that expresses CD14 less intensely, but with an increased expression of CD16 on the cell membrane (CD14 + CD16 + ). 32,33 This subset also seems to be distinct from regular blood monocytes, since they produce less TNF, IL-1b and IL-6 34 and may represent an early stage of differentiation towards alveolar macrophages. Another possibility is that GM-CSF promotes differentiation of monocytes towards antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 98%
“…Yet, we provide new evidence for a functional immaturity of monocytes at this stage. High expression of CD16 on monocytes has been shown to correlate with increased clearance of pathogens at the site of infection [11][12][13]15], which may help compensate for the lack of IL-1β in the early neonatal period. On the other hand, the lack of LPS-mediated pro-IL-1β response in CD14 low monocytes potentially represents an early developmental stage at which monocyte IL-1β responses are dispensable.…”
Section: Discussionmentioning
confidence: 99%
“…These CD14 high /CD16 neg monocytes make up the majority of monocytes in peripheral adult blood, and have been proposed to be capable of producing high amounts of IL-10 [11]. In contrast, the smaller, nonclassical CD14 low /CD16 pos monocytes express high levels of the antigenpresenting molecule HLA-DR [12], as well as cytokine TNF-α [13]. This latter subset has been proposed to play an important immediate responder "proinflammatory" role in sepsis [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in the context of phenotype-function relations, Ziegler-Heitbrock el al. showed that the small subset of normal monocytes co-expressing CD 14 dimly and CD 16 brightly have a lower phagocytic capacity and a lower stimulated cytokine production [43], On the other hand, Capsoni et al showed a decreased antibody-mediated phagocytosis by monocytes from AIDS patients, despite an increased density of FC7RI, an increased proportional expression of FC7RIII, and elevated levels of IFN-7 [44].…”
Section: Co-expression Of CD 14 Fcyri and Cdllb But Not Fey Riiimentioning
confidence: 99%